(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
In This Scientific Paper it had been studied the Effect of Ponderomotive Force on Landau damping of electron Wave in dense quantum Plasmas, by Using quasi quantum kinetic Equation, Using the Corrections due to both of quantum effects and Ponderomotive Force, because of their necessity in Studying Wave Reflection inside Cavity Energy ,and some Physical Properties of Plasmas, then comparing the Results to the other Conclusions in this Field.